Pengaruh Korean Wave, Sosial Media, Influencer Marketing terhadap Keputusan Pembelian pada Conveniences Store K3 Mart - Vindi Julia Anggraini; Rezky Aulia Pramudita (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to analyze the influence of the Korean Wave, social media, and influencer marketing on consumer purchasing decisions at K3 Mart Surabaya. The Korean Wave phenomenon, which includes K-pop, K-drama, and Korean products such as cosmetics and food, has gained significant attention from Indonesian consumers, particularly among the younger generation. Coupled with the growing role of social media in everyday life and marketing strategies through influencer marketing, these three factors are believed to impact consumer purchasing decisions. The research used a quantitative method, collecting data through questionnaires distributed to 105 respondents. Data analysis was conducted using SPSS 27, including validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results indicate that the Korean Wave, social media, and influencer marketing have a significant positive influence on purchasing decisions at K3 Mart. Partially, the Korean Wave has the most dominant effect on purchasing decisions, followed by social media and influencer marketing. Simultaneous tests also show that all three independent variables significantly influence purchasing decisions. The Adjusted R Square value of 0.702 indicates that 70.2% of the variation in purchasing decisions can be explained by these three variables. These findings suggest that marketing strategies leveraging the Korean Wave, social media, and influencer marketing can enhance consumer purchasing decisions, particularly among the younger generation who are more influenced by digital trends and popular culture. This research provides insights for businesses, especially in the retail sector, to optimize the use of these three elements in formulating their marketing strategies.